INVALOR (Counselor Service Innovation): Cyber Counseling Application with Comprehensive Counseling Model As A Student’s Academic Planning in the Era of Society 5.0 - Dwi Wahyuningtyas; Panji Nur Fitri Yanto; Zaenab Amatillah Rhodiyya; Rafina Sekar Arsanti; Caraka Putra Bhakti (Journal of Indonesian Progressive Education, 2024)
Almost all parts of the world are currently being hit by the outbreak of the Coronavirus Disease (Covid-19) which has a profound impact in the field of education is to change the process of face-to-face learning in schools to become online learning. As the main practitioner of guidance and counseling services, they must also keep up with industry developments into the Society 5.0 era. The implementation of long distance counseling can be done using Cyber Counseling techniques. As for this scientific paper, the authors use the literature review method and the Research and Development (RnD) model with a 4D model (Define, Design, Development, and Dissemination) and SWOT analysis to assist in providing an interpretation of the ideas and ideas that have been planned. Therefore, the purpose of writing this scientific paper is to find out the concepts, principles, and effectiveness of Society 5.0, Cyber Counseling, Comprehensive Counseling, and Academic Planning for Students. It is hoped that the INVALOR application can be useful for guidance and counseling services in a more advanced era in preparing superior and competent Indonesian students, as well as mastering the skills needed in this 5.0 society era so that students have a competitive spirit to survive and compete globally.